Texicalaan: A Memory Called Empire - Book 1 - Martine, Arkady (Tor, 2019)
"During a time of political instability in the highest echelons of the imperial court, Ambassador Mahit Dzmare arrives in the center of the multi-system Teixcalaanli Empire only to discover that her predecessor, the previous ambassador from their small but fiercely independent mining Station, has died. But no one will admit that his death wasnt an accident--or that Mahit might be next to die. Now Mahit must discover who is behind the murder, rescue herself, and save her Station from Teixcalaans unceasing expansion--all while navigating an alien culture that is all too seductive, engaging in intrigues of her own, and hiding a deadly technological secret--one that might spell the end of her Station and her way of life--or rescue it from annihilation"--From publisher.
Keywords: Fiction; Murder; Fiction; Extraterrestrial beings; Fiction; Ambassadors; Science fiction; Science fiction